(untitled) - Schildt, Herbert (New York, 2008)
Legendary programming author Herb Schildt shares some of his favorite programming techniques in this high-powered Java "cookbook." Organized for quick reference, each recipe shows how to accomplish a practical programming task. A recipe begins with a list of key ingredients (the classes, methods, and interfaces) followed by step-by-step instructions that show how to assemble them into a complete solution. Detailed discussions explain the how and why behind each step, and a full code example puts the recipe into action. Each recipe ends with a list of options and alternatives that suggest ways to adapt the technique to fit a variety of situations. Whether you're a beginner or an experienced pro, you'll find recipes that are sure to satisfy your Java programming appetite!
Keywords: Java (Computer program language),Java (Ngôn ngữ lập trình)